SISTEM E-WISATA PADA DINAS PARIWISATA DI KOTA PEKANBARU BERBASIS ANDROID - Rika Melyanti; Muhardi .; Yose Andreas (STMIK Hang Tuah Pekanbaru, 2017)
The use of smartphones using the android operating system now is greatly improved, this smartphone device can all be done with a variety of embedded applications or that will be downloaded at flatform available. with ease in this android device users can access all kinds of information about attractions, hotels and culinary in Pekanbaru. Moreover, in the current discourse on development of tourist information in Indonesia are very vigorous in order for domestic and foreign tourists coming to Indonesia to see tourism in indonesia. In this tourism city of Pekanbaru do activities to develop tourism in the city of Pekanbaru to be known and can be visited by tourists. In order to be known and visited by tourists with the use of applications of E-tourism in the city of Pekanbaru, tourist spots, hotels and culinary in Pekanbaru easily accessible simultaneously on your android device already installed applications E-city tours Pekanbaru. With the ease of the application it will facilitate travelers to select tourist attractions, hotels and culinary in Pekanbaru. This application is very useful for supporting information to be provided by the Tourism Office of the city of Pekanbaru, and would be likely to be application that provides information on travel destinations and simultaneously accessing the nearby residence while existing in Indonesia as a whole and detail.